2016
DOI: 10.1039/c6np00015k
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ecology of marine plankton

Abstract: Covering: January 2013 to online publication December 2014This review summarizes recent research in the chemical ecology of marine pelagic ecosystems, and aims to provide a comprehensive overview of advances in the field in the time period covered. In order to highlight the role of chemical cues and toxins in plankton ecology this review has been organized by ecological interaction types starting with intraspecific interactions, then interspecific interactions (including facilitation and mutualism, host-parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 119 publications
0
29
0
2
Order By: Relevance
“…Natural plankton communities may include multiple diatom and non-diatom populations producing a variety of bioactive secondary metabolites (e.g., Strom 2008;Ianora et al 2012;Schwartz et al 2016). For example, S. marinoi growth was inhibited in the presence of a domoic acid-producing strain of P. delicatissima (Prince et al 2013).…”
Section: Mesozooplankton Responsementioning
confidence: 99%
“…Natural plankton communities may include multiple diatom and non-diatom populations producing a variety of bioactive secondary metabolites (e.g., Strom 2008;Ianora et al 2012;Schwartz et al 2016). For example, S. marinoi growth was inhibited in the presence of a domoic acid-producing strain of P. delicatissima (Prince et al 2013).…”
Section: Mesozooplankton Responsementioning
confidence: 99%
“…Nevertheless, based on the extremely complex symbiotic relationship between plants and microbes, more work is still needed in order to better understand the important interactions between the inter- or intra-players of ecosystem function, plants and their associated microorganisms. Recent evidence showed that chemical ecology is a robust and efficient methodology to uncover the behavior and ecological functions of microbes (Schwartz et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…This study emphasises that the environment within which the animal lives is central to the cues received to inform the behavioural trade-offs that balance risk and vigilance against other fitness promoting activities. Recent research emphasises the importance of water-borne chemicals for aquatic organisms, and that chemical information can play a central role in key behavioural decisions associated with antipredator responses 56 , 57 . Chemicals that are passively or actively released into the surrounding water contain ecologically relevant information that includes reproductive state 58 , 59 , stress 60 , disturbance 61 , habitat suitability and availability 62 , 63 , and the type, size and quality of a prey item 64 .…”
Section: Discussionmentioning
confidence: 99%